2017
DOI: 10.1123/jis.2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

Front Porch, Small House: A Longitudinal Study of Team and University Identification Among Incoming Students at a Division III University

Abstract: In this longitudinal study, the authors examined the relationship between team identification and university identification for 37 incoming college first year students at a National Collegiate Athletic Association (NCAA) Division III institution. After collecting four waves of data from the same participants over the course of two years, the authors utilized growth curve analysis to examine the development and trajectories of the students' levels of identification with both the university and the intercollegia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A student's peer relationships are the single best predictor of success in college (Astin, 1999) -and for the participants in this study, the presence of Division III sports on campus assisted in the evolution of incoming friendship ties. Katz et al (2017) stated that Division III sports represent the front porch of a small house in terms of promoting attitudes toward the larger university for new students. We extend that sentiment, showing that fan ties affect friendships and social integration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A student's peer relationships are the single best predictor of success in college (Astin, 1999) -and for the participants in this study, the presence of Division III sports on campus assisted in the evolution of incoming friendship ties. Katz et al (2017) stated that Division III sports represent the front porch of a small house in terms of promoting attitudes toward the larger university for new students. We extend that sentiment, showing that fan ties affect friendships and social integration.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Katz and Clopton (2014) found that identification with Division III athletic teams contributed to students' increased identification with the surrounding community. Katz, Dixon, Heere, and Bass (2017) also examined the Division III setting, suggesting Division III athletics serve as a "front porch" for new students. More specifically, they found that growth trajectories of team identification significantly affected changes in university identification.…”
Section: Sport Consumer Behavior: Fan Network and Sports On Campusmentioning
confidence: 99%
See 1 more Smart Citation
“…College sports have been utilized to facilitate students' involvement on campus, leading to active social engagement with peers (Davis et al, 2020;Katz & Heere, 2016;Katz et al, 2017). More specifically, studies have shown how students in higher education utilize varsity athletics to feel more attachment and belonging within their campus community (Heere & Katz, 2014;Katz & Heere, 2016;Sung et al, 2015).…”
Section: The Effect Of Team Identification On Sense Of Community and ...mentioning
confidence: 99%
“…In an empirical review of research related to intercollegiate athletics, Goff (2000) summarized studies focused on financial impacts, media exposure, donor giving, and student enrollment. Intercollegiate athletics' position as the so-called front porch, or "the most visible room in the house" (Katz et al, 2017, p. 105), and its relationship to other facets of higher education also has been studied extensively (Bass et al, 2015;Katz et al, 2017).…”
Section: Overview Of Relevant Literaturementioning
confidence: 99%